The Development of the Dutch Colonial Settlement in the City of Yogyakarta after the Implementation of the Decentralisatie Wet Policy (1903-1942) - Dimas Wihardyanto; Ahmad Sarwadi; Achmad Djunaedi (Jurnal Arsitektur, 2023)
Decentralization wet or the law on decentralization of development was one of the policies that had a significant effect on the development of Indonesia during the Dutch colonial period, including residential areas for Europeans. This study tries to reveal the pattern of development of Dutch colonial settlements in the city of Yogyakarta by using interpretative historical research methods on cartographic, architectural, and textual archival data that are relevant to the research theme. Based on the results of the analysis conducted by the researcher, it is known that the growth of the Dutch colonial settlement area in the city of Yogyakarta after the application of decentralization wet began with the emergence of residential areas supporting rail transportation facilities and followed by residential areas supporting public facilities. Furthermore, when transportation and public facilities are established, this will trigger the further growth of the Dutch colonial settlement area. From the results of the research, it is also known that there are three types of Dutch colonial settlements in the city of Yogyakarta based on the pattern used. The three types are open and semi-open settlement types which are intended for most Europeans, as well as closed settlement types which are intended for amtenaar (civil servants). The panel also found that the existence of an open space in the form of a garden or other function in the middle of the Dutch colonial settlement area was one of the factors that caused this area to be felt to have a higher and more luxurious degree compared to other residential areas because it could better guarantee the existence of better air circulation. better so that the houses around it are more comfortable to be lived.